Local pesticide use intensity conditions landscape effects on biological pest control. Issue 1904 (12th June 2019) - Ricci, B.; Lavigne, C.; Alignier, A.; Aviron, S.; Biju-Duval, L.; Bouvier, J. C.; Choisis, J.-P.; Franck, P.; Joannon, A.; Ladet, S.; Mezerette, F.; Plantegenest, M.; et al.
Abstract : Complex landscapes including semi-natural habitats are expected to favour natural enemies thereby enhancing natural pest biocontrol in crops. However, when considering a large number of situations, the response of natural biocontrol to landscape properties is globally inconsistent, a possible explanation being that local agricultural practices counteract landscape effects. In this study, along a crossed gradient of pesticide use intensity and landscape simplification, we analysed the interactive effects of landscape characteristics and local pesticide use intensity on natural biocontrol. During 3 years, using a set of sentinel prey (weed seeds, aphids and Lepidoptera eggs), biocontrol was estimated in 80 commercial fields located in four contrasted regions in France. For all types of prey excepted weed seeds, the predation rate was influenced by interactions between landscape characteristics and local pesticide use intensity. Proportion of meadow and length of interface between woods and crops had a positive effect on biocontrol of aphids where local pesticide use intensity was low but had a negative effect elsewhere. Moreover, the landscape proportion of suitable habitats for crop pests decreased the predation of sentinel prey, irrespectively of the local pesticide use intensity for weed seeds, but only in fields with low pesticide use for Lepidoptera eggs. These results show that high local pesticide use can counteract the positive expected effects of semi-natural habitats, but also that the necessary pesticide use reduction should be associated with semi-natural habitat enhancement to guarantee an effective natural biocontrol.